Self-Compassion in Obese Female Students Whom Experienced Body Shaming - Mangarengi, Yusyah Alreffyanny; Murdiana, Sitti (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
Obese female students are prone to experiencing psychological problems due to receiving body shaming from the environment, therefore obese female students carry out self-monitoring to avoid the psychological impact of body shaming. This study aims to determine the relationship between self-compassion and body shaming in obese female students in Makassar. The method used in this research is correlational quantitative method. The research subjects totaled 150 subjects with the subject of research criteria namely obese female students in Makassar City aged 18-25 years and experiencing body shaming. The outcomes revealed that the significance value was p = 0.000 (p <0.05) and the correlation coefficient r = -0.542 indicated that there was a negative relationship between self-compassion and body shaming in obese female students in Makassar, which means that the higher the self-compassion of obese female students, the lower the body shaming of obese female students. This research is likely to generate encouragement for obese female students to apply self-compassion to accept and love themselves.Mahasiswa perempuan obesitas rentan mengalami masalah psikologis akibat menerima tindakan body shaming dari lingkungan oleh karena itu mahasiswa obesitas melakukan pengawasan diri untuk menghindari dampak psikologis dari tindakan body shaming. Tujuan daripada penelitian ini yakni untuk mengetahui hubungan self-compassion dengan body shaming pada mahasiswa perempuan obesitas di kota Makassar. Metode yang digunakan dalam penelitian ini adalah metode kuantitatif korelasional. Subjek penelitian berjumlah 150 subjek dengan kriteria subjek penelitian yaitu mahasiswa perempuan obesitas di Kota Makassar berusia 18-25 tahun, dan mengalami body shaming. Hasil studi tersebut menunjukkan bahwa nilai signifikansi adalah p = 0,000 (p kurang dari 0,05) dan koefisien korelasi adalah r = -0,542 membuktikan bahwa terdapat hubungan yang negatif antara tingkat self-compassion dan body shaming pada mahasiswi perempuan yang mengalami obesitas di Kota Makassar. Artinya, semakin besar tingkat self-compassion yang dimiliki oleh mahasiswi perempuan yang mengalami obesitas, semakin rendah pula tingkat body shaming yang dialami oleh mereka. Implikasi penelitian ini adalah agar mahasiswa perempuan obesitas dapat menerapkan self-compassion dalam menerima dan mencintai diri sendiri.